Problematika Guru dalam Menentukan Metode Belajar yang Tepat - Vitra Anugrah Lubis; Dea Fitri Ananda Sormin; Nelly Trioctavia Manik; Anggun Trianiysah Juli; Rahmilawati Rahmilawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Elementary school-aged children have unique characteristics, such as enjoying play, movement, group activities, and hands-on learning. Most students at this age prefer practical activities over theoretical instruction. Therefore, primary education aims to support and develop children's growth in accordance with their developmental tasks. Elementary school teachers play a crucial role in integrating these developmental needs into the learning process. The implementation of education at the elementary level must align with national regulations and policies, including standards for management, assessment, facilities, final examinations (UASBN), and teacher qualifications. Learning evaluation is a critical component in ensuring educational quality. However, in practice, teachers often face challenges such as limited time and a lack of understanding in assessing affective and psychomotor domains. As a result, solutions such as teacher training and more effective classroom management are necessary. This study aims to identify the challenges and proposed solutions related to the implementation of learning evaluations in elementary schools based on interviews with educational practitioners.